The Value of Energy Efficiency and the Role of Expected Heating Costs - Andreas Mense (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The German Energy Performance of Buildings Directive requires sellers on the housing market to provide detailed information on expected yearly energy consumption per square meter. This paper uses variation in local fuel prices and climate, fuel types, and building ages to analyze the relationship between expected energy cost savings from energy efficient building structure and house prices in Germany. Results suggest that heating cost considerations are less relevant than previously thought.
Keywords: R21; R31; Q40; 330